Development of an Inventory for Health-Care Office Staff to Self-Assess Their Patient-Centered Cultural Sensitivity - Carolyn M. Tucker; Whitney A. Wall; Guillermo Wippold; Julia Roncoroni; Michael M. Marsiske; Gabriel S. Linn (SAGE Publishing, 2016)
Background: Patient-centered culturally sensitive health care (PC-CSHC) is a best practice approach for improving health-care delivery to culturally diverse populations and reducing health disparities. Despite patients' report that cultural sensitivity by health-care office staff is an important aspect of PC-CSHC, the majority of available research on PC-CSHC focuses exclusively on health-care providers. This may be due in part to the paucity of instruments available to assess the cultural sensitivity of health-care office staff. The objective of the present study is to determine the psychometric properties of the Tucker-Culturally Sensitive Health Care Office Staff Inventory-Self-Assessment Form (T-CSHCOSI-SAF). This instrument is designed to enable health-care office staff to self-assess their level of agreement that they display behaviors and attitudes that culturally diverse patients have identified as office staff cultural sensitivity indicators. Methods: A sample of 510 health-care office staff were recruited at 67 health-care sites across the United States. These health-care office staff anonymously completed the T-CSHCOSI-SAF and a demographic data questionnaire. Results and Level of Evidence: Confirmatory factor analyses of the T-CSHCOSI-SAF revealed that this inventory has 2 factors with high internal consistency reliability (Cronbach's αs= .916 and .912). Conclusion and Implications: The T-CSHCOSI-SAF is a useful inventory for health-care office staff to assess their own level of patient-centered cultural sensitivity. Such self-assessment data can be used in the development and implementation of trainings to promote patient-centered cultural sensitivity of health-care office staff and to help draw the attention of these staff to displaying patient-centered cultural sensitivity.